Research and development of intelligent gateway for wireless body area networks in healthcare - Peh, Chong Yi. (2012)
The innovation of Wireless Body Area Network (WBAN), which is made up of sensor nodes attached around a user’s body, has introduced a whole area of research in finding practical ways to deploy them in people’s daily lives. In this project, the area of focus for deploying WBAN would be in the area of healthcare where a user’s health statistics such as heart rate, blood pressure and etc., can be obtained by the sensor nodes attached around him. These statistical data can then be used for monitoring purposes or to administer an action pertaining to the health condition of the user. By using WBAN in conjunction with the internet, this can be extremely useful for patients whom require real time monitoring of their health conditions by their physicians who might not be able to be physically present with them. In the case of an emergency, the physicians can immediately inform the patient by sending appropriate instructions.